2019
DOI: 10.1088/1742-6596/1376/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Zeolite Lynde Type A (LTA): Effect of Aging Time

Abstract: Zeolite Lynde Type A (LTA) has been widely applied, such as adsorbent, catalyst, membrane, ion exchanger, and even molecular sieve. As molecular sieve, the zeolite LTA has high dehydration ability and has a prospect as separation agent such as water removal from the ethanol-water mixture to obtain high purity bioethanol. Furthermore, it can repeatedly be used, lower energy usage, and environmentally friendly. Due to the number of advantages possessed, this research conducted to synthesize the zeolite LTA. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The aging time at room temperature influenced the formation of the zeolite crystal nuclei and the crystallization rate [45]. In this study, the effect of varying the aging time was evaluated, which ranged between 18 and 32 h. It was demonstrated that the higher time used for aging, the higher content of zeolite was obtained.…”
Section: Effect Of the Aging Time On The Synthesis Of Zeolite Ltamentioning
confidence: 97%
“…The aging time at room temperature influenced the formation of the zeolite crystal nuclei and the crystallization rate [45]. In this study, the effect of varying the aging time was evaluated, which ranged between 18 and 32 h. It was demonstrated that the higher time used for aging, the higher content of zeolite was obtained.…”
Section: Effect Of the Aging Time On The Synthesis Of Zeolite Ltamentioning
confidence: 97%
“…Naturally occurring silicas found in agricultural waste are a good substitute for commercial silica precursors. Thus, raw materials from agricultural waste, such as corncob-stalk-and-leaves ash [ 12 ], rice husk ash [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], sugar cane bagasse ash [ 25 , 26 ], barley ash [ 27 ], coal ashes [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ], clay minerals [ 35 , 36 , 37 , 38 , 39 , 40 ], industrial slags [ 41 ], natural zeolites [ 42 ], and solid waste incineration ashes [ 43 , 44 , 45 ], are used as alternative and cheap source materials for the synthesis of zeolite. The use of agricultural waste materials, such as those in the field of water purification and in the removal of ammonium or heavy metals, makes them appealing as useful products that contribute to the mitigation of environmental problems.…”
Section: Introductionmentioning
confidence: 99%